Pengaruh Harga dan Kualitas Produk Terhadap Loyalitas Konsumen Delovely Beauty Expert Surabaya - Ayu Qolidatul Rizikia; Aisyah Darti Megasari; Komarun Zaman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Skincare encompasses both external product use and internal health practices such as a balanced diet, avoiding smoking and alcohol, stress management, and adequate sleep. The government's role in regulating skincare products is essential due to the prevalence of non-compliant products in the market. The Food and Drug Administration (BPOM) ensures product safety and quality through certification and labeling. Price, broadly defined, includes not only the monetary value paid to acquire a product but also external factors such as search effort, psychological risk, and additional costs. Product quality is a distinguishing feature that meets consumer expectations and is crucial for business growth. Delovely Beauty Expert, established by Dr. Chelsea Adikoeseomo, is an aesthetic clinic in Surabaya aiming to deliver satisfying services with aesthetic facilities, friendly service, and competent experts. Recent data from Delovely Beauty Expert's Pasar Kembang branch shows a daily increase in consumer numbers over five days, presenting a challenge to continuously develop human resources to maintain high service standards. Given the importance of clear and healthy skin for confidence and the demand for affordable and high-quality products, this study investigates the impact of price and product quality on consumer loyalty at Delovely Beauty Expert, Pasar Kembang, Surabaya.